A Solution to Multi-Objective Optimal Power Flow Using Hybrid Cultural-Based Bees Algorithm - Sumpavakup, C.; Srikun, I.; Chusanapiputt, S. (2012 Asia-Pacific Power and Energy Engineering Conference, 2012)
This paper presents a hybrid Cultural-based Bees Colony Algorithm for solving a multi-objective Optimal Power Flow (OPF). The multi-objective OPF was formulated for tackling with total generation cost and environmental impacts simultaneously. The proposed method was applied to the standard IEEE 30-bus test system. The results show that solving the multi-objective OPF problem by the Cultural-based Bee Colony are more effective than other swarm intelligence methods in the literature.